2015
DOI: 10.1080/02640414.2015.1018929
|View full text |Cite
|
Sign up to set email alerts
|

Home advantage in soccer – A matter of expectations, goal setting and tactical decisions of coaches?

Abstract: In soccer, home teams win about 67% of decided games. The causes for this home advantage are still unresolved. There is a shortage of research on the psychological states of actors involved. In this study, we examined soccer coaches' expectations, goal setting and tactical decisions in relation to game location. Soccer coaches (N = 297) with different expertise levels participated in an experimental, online management game and were randomly assigned to one of two groups, "home game (HG)" or "away game." Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 41 publications
2
55
1
6
Order By: Relevance
“…The general scientific evidence supports the fact that teams implement a more offensive style of play and achieve more goals [46] and more effectiveness to create scoring opportunities [22] when playing at home rather than away. The study of Staufenbiel, Lobinger and Strauss [47] found how coaches had greater winning expectative, established more ambitious objectives and a more offensive strategy when playing at home. This fact may be related to the higher offensive deployment in terms of more shots, dribbles and passes [48], as well as more complex and structured attacking patterns [49].…”
Section: Discussionmentioning
confidence: 99%
“…The general scientific evidence supports the fact that teams implement a more offensive style of play and achieve more goals [46] and more effectiveness to create scoring opportunities [22] when playing at home rather than away. The study of Staufenbiel, Lobinger and Strauss [47] found how coaches had greater winning expectative, established more ambitious objectives and a more offensive strategy when playing at home. This fact may be related to the higher offensive deployment in terms of more shots, dribbles and passes [48], as well as more complex and structured attacking patterns [49].…”
Section: Discussionmentioning
confidence: 99%
“…Starting with the seminal work of Schwartz and Stephen [35] in 1977, the "home advantage phenomenon" has motivated several investigations ever since [36][37][38]. A non-exhaustive list of sports where this phenomenon has been found include soccer [39][40][41][42][43][44][45], baseball [46,47], ice hockey [48,49], roller-hockey [50], basketball [51,52], rugby [53], Australian football [54], water polo [55], volleyball [56], handball [57][58][59], and cricket [60]. This effect has also been observed in individual competitions of tennis [61,62], golf [62], Winter Olympics sports [63], Summer Olympics sports [64], and several other individual sports [65].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that home teams have a more offensive style of play and more attacking production than away teams (Lago-Peñas, & Lago Ballesteros, 2010;Almeida, & Volossovitch, 2017), as well as more complex and structured attacking patterns (Diana, et al, 2017). These findings may be due to the fact that teams have greater winning expectative, more ambitious objectives and a more offensive strategy when playing at home (Staufenbiel, et al, 2015).…”
Section: Discussionmentioning
confidence: 92%